REACTIVITY OF N-SUBSTITUTED p-BENZO AND p-NAPHTHOQUINONEIMINE N-OXIDES TOWARD DIPOLAROPHILES (Journal of Sciences, Islamic Republic of Iran)
The dipolar cycloaddition reactivity of N-(1-naphthy1)-1,4- benzoquinoneimine N-oxide and N-phenyl-1,4- naphthoquinoneimine Noxide are investigated, The latter gives the expected adducts with common dipolarophiles such as acrylonitryle, methyl methacrylate, dimethylacetylene dicarboxylate and N-phenylmaleimide. The reactivity of the former nitrone is found to be minimal. It undergoes, however, an anomalous reaction with DMAD to give, after rearrangement, 1-(4-hydroxypheny1) 3, 3-dicarboxymethylbenzooxindole